TLC-Bioautography Profile of Ethyl Acetate Extract of 5 Bacteria Isolated from Ficus carica L Rhizosphere - Nanik Sulistyani; Iin Narwanti (Intelektual Pustaka Media Utama, 2015)
Research has been conducted on the 5 isolates of bacteria isolated from the rhizosphere of Ficus carica L as a producer of antibiotics. The previous study showed they have NRPS gene profiles that differ from each other. This study aims to determine the TLC Rf spots having inhibition activity against the growth of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The study was conducted using the 5 bacteria isolates, namely T19, T24, T25, T37 and T41. All isolates were fermented at room temperature for 14 days. Further the each broth culture was filtered and extracted using ethyl acetate. Components in the extract were separated by thin layer chromatography (TLC) with the mobile phase of chloroformmethanol (7: 3), followed by bioautography test against the S. aureus and E. coli to determine the chromatogram spots containing antibiotics. TLC results showed all isolates had different chromatogram profiles. The bioautography results showed that only isolate T25 can produce antibiotics against S. aureus. The antibiotic spot was at Rf 0.9 in the use of chloroform-methanol (7: 3) solvent system.